Measuring ICT usage among west coast fishermen: pre-test results from Port Dickson, Negeri Sembilan - Mohamed Shaffril, Hayrol Azril; Omar, Siti Zobidah; Abu Hassan, Musa; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Science Publications, 2012)
Problem statement: The government has admitted the effectiveness of ICT in bringing changes to the socio-economic aspects of the community. Groups such as farmers, entrepreneurs, rural community and housewives for examples have been proven by a number of past studies to profit the huge advantages offered by ICT. Nonetheless, there is inadequacy in term of study related to ICT usage among one of the important groups in Malaysia; the fishermen. Before doing a study related to ICT usage among fishermen, a reliable instrument is needed, hence the main purpose of this study is to discuss the reliability and validity of an instrument developed for measuring ICT usage among the fishermen. Approach: This is a quantitative study; the pre-test process took place at Port Dickson, Negeri Sembilan, Malaysia, where a total of 30 registered fishermen were randomly chosen as the respondents. Results: Reliability analysis run has generated cronbach alpha value ranging from 0.714-0.970 thus reflect the instrument has a good strength in term of reliability. Conclusion/Recommendations: A number of recommendations have been highlighted which involves trainings to enumerator and a number of modifications on the instrument.